ANALISIS PEMETAAN BUDAYA ORGANISASI MENGGUNAKAN ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI) PADA UNIVERSITAS ISLAM NEGERI (UIN) WALISONGO SEMARANG - Tri Wahyuningsih, Thoyyibah; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2015)
University is a part of education that produced educated employee who are able to fulfill the requirement of labor market. Islamic State of University (UIN) Walisongo Semarang were one of university that makes change from institute to University. It is done to keep demand of people needed and abreast of time, especialy the development in labor market. The purpose of this research is to do the culture mapping recently and expected future by all of stakeholder in order to it can be as recommendation to institute, have the culture recently and expected future This research used the Organizational Culture Assessment Instrument (OCAI) method. Survey was done by employees, lectures, and university students using descriptive quantitative approach. The result of this research is there was a similar of organization culture curently and expected future. That sense by stakeholder, such as employees, lectures, and university students who said that profile of Islamic State University (UIN) Walisongo Semarang currently and expected future was clan culture. There was tendency to clan culture that powerful as type culture expected. Clan culture dominated organization culture in UIN Walisongo releted to religious value that had UIN Walisongo since before change. In UIN Walisongo, it prioritised role or attitude silaturahmi, sincere, shidiq and humble and there were islamic organization culture that was taken from the resource of islamic law such as, Al Quran And Al Hadist Rasulullah SAW. This organization culture mapping can be reference UIN Walisongo to determine principle that accorded with vission, missions and purposes UIN Walisongo.